2010
DOI: 10.2353/ajpath.2010.090887
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Background Affects Properties of Satellite Cells and mdx Phenotypes

Abstract: Duchenne muscular dystrophy (DMD) is the most common lethal genetic disorder of children. The mdx (C57BL/10 background, C57BL/10-mdx) mouse is a widely used model of DMD, but the histopathological hallmarks of DMD, such as the smaller number of myofibers, accumulation of fat and fibrosis, and insufficient regeneration of myofibers, are not observed in adult C57BL/10-mdx except for in the diaphragm. In this study, we showed that DBA/2 mice exhibited decreased muscle weight, as well as lower myofiber numbers aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
186
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(198 citation statements)
references
References 44 publications
10
186
2
Order By: Relevance
“…Ten measurements were recorded, which were separated by 10‐min rest periods. The two highest and two lowest values were discarded from these measurements, and the remaining six values were averaged (Fukada et al., 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Ten measurements were recorded, which were separated by 10‐min rest periods. The two highest and two lowest values were discarded from these measurements, and the remaining six values were averaged (Fukada et al., 2010). …”
Section: Methodsmentioning
confidence: 99%
“…The D2 strain was previously noted to disrupt myoblast fusion in the mdx mouse model, and there are other QTLs that modify muscular dystrophy in the D2 strain (31,32). Membrane repair and membrane fusion share some of the same molecular machinery (33).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this rationale, Fukada and colleagues found that mice of the DBA/2 genetic background displayed impaired muscle regeneration and satellite cell self-renewal compared to other mouse strains [28]. They generated DBA/2- mdx mice and reported reduced muscle weight, fewer muscle fibers, increased fibrogenic and adipogenic accumulation and greater muscle weakness compared to the commonly used mdx mice of the C57BL/10 background.…”
Section: Dmd Is Also a Stem Cell Diseasementioning
confidence: 99%